Utilisation of Jambi Malay Prologue in Local Content Curriculum Development at Jambi University - Andiopenta Andiopenta; Ade Bayu Saputra; Deri Rachma (Yayasan Adra Karima Hubbi, 2024)
Background. Jambi Malay is rich in expressions that can be utilised as teaching materials in the development of local content curriculum in the field of culture. Purpose. The purpose of this study is to provide information on how the use of various propologue expressions in the Jambi Mekayu language can be used as local content teaching materials characterised by Jambi Malay regionalism. Method. This research uses a qualitative descriptive method. The data comes from documentation and data from informants. The data were collected using documentation and simak libat cakap. Data analysis used Hubermans’ flow technique; data presentation, data reduction, and conclusion drawing. The data validity technique used triangulation of theory and method. Results. The development of the local content curriculum must be based on the identification of regional needs and conditions, and pay attention to the principles of effectiveness, efficiency, community, and flexibility. The function of local content in Jambi Province includes cultural preservation, skills enhancement, and entrepreneurial motivation. The determination of study materials and local content subjects must be in accordance with the development of students, the ability of teachers, and available facilities, and not conflict with religious norms and social values. The development of syllabi, competency standards, and basic competencies needs to involve various parties and refer to national content standards. The use of Jambi Malay prologue expressions as teaching materials can enrich the culture-based local content curriculum. Conclusion. Expressions in Jambi Malay are very diverse, can take the form of phrases, clauses, and sentences. The meaning of expressions in Jambi Malay contains a very diverse meaning, both denotative, connotative, and meaning that is born structurally and grammatically.